EVALUASI KINERJA PEMERINTAH DESA DALAM MENGELOLA OBJEK WISATA PANTAI KETAPANG DI DESA SUNGAI CINGGAM KECAMATAN RUPAT KABUPATEN BENGKALIS - Aziz, Andi Abdul; Iskandar, Iskandar; Rahmat, Yogie (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to determine the performance of the village government in managing the Ketapang beach tourist attraction in Sungai Cinggam Village, Rupat District, Bengkalis Regency. With tourism, of course, it will bring various impacts in various aspects including environmental, socio-cultural and economic impacts. In terms of economy, tourism brings various impacts including environmental impacts, indirect impacts, and continued impacts. The direct impact is for workers in the tourist area including the local government. One of the indirect impacts can be in the form of increasing demand for public transportation. And the ongoing impact is certainly related to the government and the community who work in the tourism sector or not directly but get a positive impact. Therefore, the government, both the local government and the village government are required to manage the existing potential for the welfare of the community. This study uses a qualitative research method. The results of the study concluded that so far the quality of service and responsibility by the government in managing tourist attractions is still considered by the community to be lacking, because there are several things that the government needs to pay attention to, such as the facilities available at the tourist attraction location, because the community considers that the process of managing this tourist attraction needs attention. Keywords: Performance, Village Government, Tourist Attractions.